2018
DOI: 10.1016/j.ultramic.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

A systematic comparison of on-axis and off-axis transmission Kikuchi diffraction

Abstract: The capabilities of the novel on-axis transmission Kikuchi diffraction (TKD) technique were explored in a systematic comparison with conventional off-axis TKD. The effect of experimental parameters on the appearance of on-axis and off-axis Kikuchi patterns was measured and discussed. In contrast to off-axis TKD, on-axis TKD is more sensitive to changes in beam current and beam energy and less sensitive to changes in working distance and detector distance. Moreover, on-axis TKD has a distinct advantage over off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…On the other hand, less scattering events lead to a smaller electron beam broadening, and thus to a lower spatial The spatial resolution of the on-axis TKD was better than that of the off-axis TKD at the same accelerating voltage and thickness; the largest gap was 8 nm. The only difference between the two configurations was the intersection angle between the phosphor screen and incident beam (α) [5]. In the off-axis TKD, the intersection angle had a magnitude of only a few degrees, which led to a high gnomonic distortion and low diffraction intensity.…”
Section: Effects Of the Accelerating Voltage And Specimen Thickness Omentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, less scattering events lead to a smaller electron beam broadening, and thus to a lower spatial The spatial resolution of the on-axis TKD was better than that of the off-axis TKD at the same accelerating voltage and thickness; the largest gap was 8 nm. The only difference between the two configurations was the intersection angle between the phosphor screen and incident beam (α) [5]. In the off-axis TKD, the intersection angle had a magnitude of only a few degrees, which led to a high gnomonic distortion and low diffraction intensity.…”
Section: Effects Of the Accelerating Voltage And Specimen Thickness Omentioning
confidence: 99%
“…At a given depth, the path length through the sample is smaller for the on-axis TKD, which implies that fewer scattering events may occur before the electrons reach the detector. Therefore, the on-axis TKD has a thicker source region of detected intensity, which is beneficial to the lateral spatial resolution, but detrimental to the depth spatial resolution [5,22].…”
Section: Effects Of the Accelerating Voltage And Specimen Thickness Omentioning
confidence: 99%
See 2 more Smart Citations
“…A better understanding of the spatial resolution, angular resolution and Kikuchi pattern formation mechanisms in TKD are still required to understand the potential and the limitations of the technique and so define how it can best be applied to addressing real materials questions at the nano-scale. A number of authors [5,7,[10][11][12] have studied the spatial resolution of TKD analysis; especially lateral resolution where it has been shown that combining high accelerating voltages and low sample thicknesses give the best results [5]. By comparison the depth resolution (dd) has been much less investigated.…”
Section: Introductionmentioning
confidence: 99%